The (16,16,2) designs - E. F. Assmus, Jr; Chester J. Salwach (International Journal of Mathematics and Mathematical Sciences)
Elementary techniques of algebraic coding theory are here used to discuss the three biplanes with k=6. These three designs are intimately related to the (16,11) extended binary Hamming code and to one another; we systematically investigate these relationships.